2012
DOI: 10.1098/rsbl.2012.0113
|View full text |Cite
|
Sign up to set email alerts
|

Social learning of a communicative signal in captive chimpanzees

Abstract: The acquisition of linguistic competency from more experienced social partners is a fundamental aspect of human language. However, there is little evidence that non-human primates learn to use their vocalizations from social partners. Captive chimpanzees (Pan troglodytes) produce idiosyncratic vocal signals that are used intentionally to capture the attention of a human experimenter. Interestingly, not all apes produce these sounds, and it is unclear what factors explain this difference. We tested the hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 20 publications
2
65
0
Order By: Relevance
“…Both claims have been challenged by recent findings. With respect to the assumption that primates lack control over voiced calls, we found, for example, that some chimpanzees display an apparently voluntary extended grunt-a voiced call-to attract attention to themselves (Leavens et al 2004;Russell et al 2013;Taglialatela et al 2012). In addition, a recent study of a gibbon demonstrated apparent voluntary control over the physical properties of the animal's larynx (Koda et al 2012).…”
Section: Primate Callsmentioning
confidence: 83%
See 1 more Smart Citation
“…Both claims have been challenged by recent findings. With respect to the assumption that primates lack control over voiced calls, we found, for example, that some chimpanzees display an apparently voluntary extended grunt-a voiced call-to attract attention to themselves (Leavens et al 2004;Russell et al 2013;Taglialatela et al 2012). In addition, a recent study of a gibbon demonstrated apparent voluntary control over the physical properties of the animal's larynx (Koda et al 2012).…”
Section: Primate Callsmentioning
confidence: 83%
“…Recently, Taglialatela et al (2012) have demonstrated that offspring of captive chimpanzees tend to acquire and use the attention-getting calls of their mothers-significantly more so than their siblings, who were equally related to their mothers, but raised apart from them. Taglialatela (2012) extended grunts (voiced, atonal sounds produced by the chimpanzees with an open mouth); kisses (produced by inhaling air through pursed lip); lip smacks (produced by placing upper and lower lips tightly together then pulling them apart quickly, making an audible "pop" sound); pants (audible, rapid, rhythmic sequence of inhaling and exhaling); raspberries (produced by blowing air out through pursed lips); and teeth chomps (produced by clacking teeth together so that the hitting together of upper and lower jaws is audible).…”
Section: Evidence From Attention-getting Callsmentioning
confidence: 99%
“…However, because these activations have so far been found only in the context of attention-getting sounds, it remains unclear as to whether they also occur during other vocalizations (Liebal et al, 2014). Interestingly, many of these attention-getting sounds were either nonvocal or idiosyncratic sounds developed by only a few individuals through their extended contacts with human caretakers and thus potentially socially learned (Taglialatela et al, 2012). This opens the possibility of these structures being involved only in the case of learned vocalizations, much like human language, as opposed to more innate and emotionally-based vocalizations.…”
Section: Vocal Communication: Productionmentioning
confidence: 99%
“…Though performed with the mouth, whistling is a non-vocal motor act requiring fine control of lip positions and airflow. Most recently, infant chimpanzees have been shown to adopt particular non-vocal sound production techniques (kisses, lip smacks, Bronx cheers, teeth clacking) as attention-getting signals based on the techniques modeled by their mothers (Taglialatela, Reamer, Schapiro, & Hopkins, 2012). Chimpanzees also can be trained to produce such non-vocal sounds, suggesting that their ability to voluntarily generate novel sounds is more flexible than previously thought (Hopkins, Taglialatela, & Leavens, 2007;Russell, Hopkins, & Taglialatela, 2012).…”
Section: Imitating Sounds Non-vocallymentioning
confidence: 99%